An emerging role for calcium signalling in innate and autoimmunity via the cGAS-STING axis. (December 2019) - Mathavarajah, Sabateeshan; Salsman, Jayme; Dellaire, Graham
Highlights: Calcium signalling plays a role in innate and autoimmunity via the cGAS-STING axis. During STING activation, TREX1 acts as a brake and cGAS the acceleration pedal. Systemic lupus erythematosus (SLE) pathology is coupled to Ca 2+ homeostasis. STING and STIM1 connect Ca 2+ homeostasis to type I interferon signaling. AMPK activation by STING links autophagy to the IFN response and relies on Ca 2+ signaling. Abstract: Type I interferons are effector cytokines essential for the regulation of the innate immunity. A key effector of the type I interferon response that is dysregulated in autoimmunity and cancer is the cGAS-STING signalling axis. Recent work suggests that calcium and associated signalling proteins can regulate both cGAS-STING and autoimmunity. How calcium regulates STING activation is complex and involves both stimulatory and inhibitory mechanisms. One of these is calmodulin-mediated signalling that is necessary for STING activation. The alterations in calcium flux that occur during STING activation can also regulate autophagy, which in turn plays a role in innate immunity through the clearance of intracellular pathogens. Also connected to calcium signalling pathways is the cGAS inhibitor TREX1, a cytoplasmic exonuclease linked to several autoimmune diseases including systemic lupus erythematosus (SLE). In this review, we summarize these and other findings that indicate a regulatory role for calcium signalling in innate and autoimmunity through the cGAS-STING pathway.